[PP.07.17] VITAMIN D RECEPTOR GENE POLYMORPHISMS, FGF-23 AND FETUIN-A IN ESSENTIAL HYPERTENSION. (September 2016) - Guarino, L.; Scazzone, C.; Arsena, R.; Vaccaro, F.; Guarneri, M.; Morreale, M.; Altieri, D.; Mulè, G.; Cottone, S.
Abstract : Objective: The association between FokI and BsmI vitamin D receptor gene (VDR) polymorphisms and cardiovascular risk was analyzed with contrasting results. Low plasmatic concentrations of fetuin-A, a negative regulator of vascular calcification, and high levels of fibroblast growth factor 23 (FGF-23), a calcium and phosphate metabolism regulator, seem to be associated with higher cardiovascular mortality. Our aim was to evaluate possible association between FokI and BsmI VDR polymorphisms and plasma concentrations of fetuin-A and FGF-23 in essential hypertension. Design and method: Seventy-one patients with essential hypertension underwent clinical blood pressure evaluation, 24-hour ambulatory blood pressure monitoring, assays of 25-hydroxyvitamin D (25[OH]D), FGF-23 and fetuin-A serum levels, and FokI and BsmI VDR polymorphisms analysis. Results: No significant correlations were found either between 25[OH]D and FGF-23, or between 25[OH]D and fetuin-A. When patients were divided according to FokI and BsmI genotypes, we did not observe any significant difference in 25[OH]D, fetuin-A and FGF23 values among different subgroups. Considering FGF-23 median value (79 pg/ml), we did not find any association between a genotype or allele and FGF-23 serum level higher than cut-off. A similar result was obtained by evaluating the association between FokI and BsmI genotypes or alleles, and fetuin-A levels lower than median value (1, 2 g/L). Conclusions: In essential hypertension FokI and BsmI VDR polymorphisms does not seem to be associated either with high FGF-23 serum levels, or with low fetuin-A plasma concentrations.